1978
DOI: 10.1002/bms.1200051213
|View full text |Cite
|
Sign up to set email alerts
|

A selective and sensitive assay for urinary metanephrine and normetanephrine using gas chromatography mass spectrometry with selected ion monitoring

Abstract: Vapor phase methodology for quantitative analysis of urine for metanephrine and normetanephrine as the pentafluoropropionyl derivative is described. The use of selected ion monitoring provided sufficient sensitivity and selectivity that milliliter aliquots of urine required only a simple scheme of sample processing; preliminary purification consisted of percolation through a column of XAD-2 followed by solvent extraction. The sample extracts were converted to the pentafluoropropionyl derivatives and analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Total urinary metanephrines are usually measured after an acid hydrolysis step or more rarely by enzyme treatment with arylsulfatase to cleave the sulfate moiety from the phenolic group [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total urinary metanephrines are usually measured after an acid hydrolysis step or more rarely by enzyme treatment with arylsulfatase to cleave the sulfate moiety from the phenolic group [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Metanephrines in free form are measured by HPLC with electrochemical or fluorimetric detection, using calibrators prepared inhouse by weighting free synthetic metanephrines or using certified calibrators provided by commercial distributors such as BioRad, Chromsystems or RECIPE [7][8][9][10][11][12][13][14][15][16][17]. It has been reported that most metanephrines present in calibrators and quality controls are free rather than sulfoconjugated forms [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation